Teori Tentang Persepsi dan Teori Atribusi Kelley - Siti Ariska Nur Hasanah; Dwi Agustina; Oktavia Ningsih; Intan Nopriyanti4 (Universitas 17 Agustus 1945 Semarang, 2024)
Kelley's perception theory and attribution theory are two main approaches in psychology that examine how individuals understand and give meaning to other people's behavior. Perception theory, based on the concept that people view the world through a subjective lens, highlights the importance of individuals' interpretations of social information in shaping their perceptions of others. In contrast, Kelley's attribution theory focuses on the way individuals explain behavior, both their own and that of others, through causal attributions to internal (such as personality) or external (such as situation) factors. By combining different psychological perspectives, these two theories provide valuable insights into the complexity and diversity of how humans understand and process social information in everyday interactions.